Edukasi Pemanfaatan Buah dan Pohon Pisang untuk Keberlajutan Nilai Ekonomi Pelaku UMKM - Susilo, Joko Hadi; Endang, Endang; Rahmawati, Laily Agustina; Suprastiyo, Ahmad; Erwanto, Erwanto; Astuti, Hartiningsih; Thohir, Muhammad Bakhru (Perkumpulan Kualitama Edukatika Indonesia, 2023)
Micro, small and medium enterprises have an important role in maintaining general economic balance in an area through increasing income in the category of community economic independence. Micro-enterprises are more directed at production carried out by households. However, there are still many problems in its operations, especially in human resources and the management of products and waste from products in a sustainable manner. In this activity, researchers use a participatory approach which is often called participatory action research (PAR). The result of this assistance is that improving the quality of knowledge of business actors can be carried out properly through providing education regarding administrative requirements that must be met by business actors in managing their business, including NPWP, NIB, PIRT, Trademarks and Halal Certification. improvement of product quality that has been carried out for business actors in this assistance through the implementation of a marketing mix strategy as expected. Utilization of tree waste and banana peels through education in this activity can run well. Utilization of banana peel waste is carried out for animal feed and this assistance can be carried out properly starting from the drying process to milling.